Implementasi Perubahan Kedua Kebijakan Pengampunan Pajak Terkait Pengungkapan Aset Sukarela Dengan Tarif Final Wajib Pajak Badan KPP Madya Jakarta Barat - Selvi Selvi (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
This study aims to analyze the implementation of the second amendment to tax amnesty policy related to disclosure of voluntary assets at the final rate of corporate taxpayers at West Jakarta Medium Tax Office. This study uses a qualitative descriptive approach. The results showed that the implementation of the second amendment to the tax amnesty policy related to the disclosure of voluntary assets with the final rate in West Jakarta Medium Tax Office according to six factors used by the authors, namely policy size and objectives, resources, communication between organizations, characteristics of implementing agents, dispositions (tendency) of the implementers, social, economic and political environments have been fulfilled. But there are some things that need to be observed, namely the target of PAS-Final policy is not appropriate for corporate taxpayers, which are due to corporate taxpayers more obedient, besides most of the corporate taxpayers have revealed their assets in tax amnesty policies, so the target should be more devoted to individual taxpayers. In addition, the participation of taxpayers to participate in this program is till lacking.